The x-intercept of function f is lower than
the x-intercept of function g.
First, we need to write the statement Function g is the sum of 2 and the cube root of the sum of three times x and 1 as a function. This is expressed as:
- g(x) = [tex]\sqrt[3]{3x+1} + 2[/tex]
- The x-intercept is the point where g(x) = 0
Substituting this g(x) = 0 into the function will give:
[tex]\sqrt[3]{3x+1} + 2 = 0\\\sqrt[3]{3x+1} = -2\\3x + 1 = -8\\3x = -9\\x = -3[/tex]
For the function f(x), the x-intercept is 3 from the given table.
Therefore, the x-intercept of function f is lower than
the x-intercept of function g.
Learn more on intercept here: https://brainly.com/question/12271239